Abrasiveness index of dispersions of Portuguese clays using the Einlehner method: influence of clay parameters. (March 2014) - A. Quintela,; Costa, C.; Terroso, D.; Rocha, F.
Abstract: The unique properties of clays make them suitable for a large number of applications. Among the procedures that can be used to characterize clayey materials, the assessment of the abrasion and the abrasiveness index can be employed to predict the mechanical behaviour of clay samples. However, only a limited number of references to these testing procedures are available in the literature. Several Portuguese clayey samples were collected and the <63 μm fraction was analysed. The main clay minerals present are kaolinite, illite and smectite. The abrasiveness index depends on the granulometric and mineralogical compositions. A lower abrasiveness is induced by the presence of a high abundance of the <2 μm fraction, small mean particle size and a large phyllosilicate content . Kaolinite and illite show good correlation with the abrasiveness index, while smectite decreases abrasion.